Epilepsy simplified - Leach, John Paul; O'Dwyer, Rebecca (Tfm Pub., 2011)
Epilepsy is a common condition which has been recognised since the beginning of history, and as the opportunities for diagnosis and effective treatment have increased, it becomes more important that health professionals have a working knowledge of how epilepsy interacts with their own area of expertise. This book deals with epilepsy.